Quand les morts reviennent… Réflexion sur l’ancestralité chez les Mayas des Basses Terres - Olivier Le Guen (Journal de la Société des Américanistes)
When the dead come home… Remarks on ancestor worship among the Lowland Mayas. In Amerindian ethnographical literature, ancestor worship is often mentioned but evidence of its existence is lacking. This article will try to demonstrate that some Lowland Maya do worship ancestors; it will use precise criteria taken from ethnological studies of societies where ancestor worship is common, compared to maya beliefs and practices. The All Souls’ Day, or hanal pixan, seems to be the most significant manifestation of this cult. Our approach will be comparative, through time – using colonial and ethnographical data of the twentieth century, and space – contemplating uses and beliefs of two maya groups, the Yucatec and the Lacandon Maya.